Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.jde.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniqueness and multi-bump solutions in parabolic problems with the p-Laplacian

Abstract: The validity of the weak and strong comparison principles for degenerate parabolic partial differential equations with the p-Laplace operator p is investigated for p > 2. This problem is reduced to the comparison of the trivial solution (≡ 0, by hypothesis) with a nontrivial nonnegative solution u(x, t). The problem is closely related also to the question of uniqueness of a nonnegative solution via the weak comparison principle. In this article, realistic counterexamples to the uniqueness of a nonnegative solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Benedikt et al [4,5] had studied the equation u t = div |∇u| p-2 ∇u + q(x) u α-1 u, (x, t) ∈ Q T , with 0 < α < 1, and such that there exists an x 0 ∈ Ω satisfying q(x 0 ) > 0. They showed that the uniqueness of a solution does not hold.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Benedikt et al [4,5] had studied the equation u t = div |∇u| p-2 ∇u + q(x) u α-1 u, (x, t) ∈ Q T , with 0 < α < 1, and such that there exists an x 0 ∈ Ω satisfying q(x 0 ) > 0. They showed that the uniqueness of a solution does not hold.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…al. [8,9] had shown that the uniqueness of the solution of the following equation is true = div (|∇ | −2 ∇ ) + ( ) | | −1 , ( , ) ∈ ( , ) ∈ Ω × (0, ) ,…”
Section: Introductionmentioning
confidence: 99%
“…There have been several papers subsequent to [10] providing non-uniqueness results for parabolic equations of various types, e.g. with unbounded coefficients [14], degenerate p-Laplacian operators [3,4,11], and systems [2,6,7,11]. However, all these works either assume explicitly that f is concave near zero [5,9] or implicitly by working only with nonlinearities of power law type, f (u) = u p (0 < p < 1).…”
Section: Introductionmentioning
confidence: 99%